(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Flutamide, a substituted anilide, is a potent antiandrogenic that has been used in the treatment of prostate carcinoma having short biological half-life of 5-6 h; thus it is a good candidate for the formulation of sustained release (SR) dosage form. The present work was focused on the preparation of matrix tablets using various polymers with different ratios. Materials and Methods: Flutamide-loaded solid dispersion was formulated by solvent evaporation, coprecipitation, co-grinding, and fusion techniques using Gelucire 50/13/polyvinylpyrrolidone K30. The developed solid dispersions were characterized for its percentage yield, drug content, morphology, and in vitro release studies. The optimized formulation was developed into an SR matrix tablet using different polymers and ratios. Furthermore, the tablets were evaluated for thickness, hardness, friability, weight variation, content uniformity, and dissolution rate, and the optimized tablet which was subjected to cytotoxic evaluation in pc3 cell lines. Results and Discussion: The obtained solid dispersion has rectangular flaky appearing particles. The dissolution rate profile of physical mixture and flutamide formulation of solid dispersions gets enhanced in comparison with the pure drug. Finally, flutamide-loaded in matrix tablets gives satisfactory pre- and post-characterization results. Conclusion: Cytotoxic evaluation of flutamide-loaded matrix tablets (at concentrations of 62.5-500 Î¼g/ml) illustrates an inhibited growth in the human prostate cancer cell line at a dose-dependent manner.